A model for the formation of complex coupling coefficients in a ring resonator of a laser gyroscope. (1st April 2022) - Petrukhin, E.A.; Bessonov, A.S.
Abstract: A model of the interference of fields from backscattering point sources in a ring optical resonator is presented. Examples of calculations of complex coupling coefficients in ring resonators of laser gyroscopes are given. Comparison of the calculation results with the results of model experiments demonstrates good agreement and makes it possible to determine dissipative and conservative backscattering components of individual resonator mirrors. The possibilities of reducing the dissipative and conservative backscattering components in the process of ring resonator alignment are discussed.